Synthesis and Preliminary Pharmacological Evaluation of Aminobenzensulfonamides Derivatives of Mefenamic Acid as a Potential Anti-inflammatory Agents - Monther F. Mahdi (College of Pharmacy University of Baghdad, 2017)
A group of amino derivatives [4-aminobenzenesulfonamide,4-amino-NÂ¹ methylbenzenesulfonamide, or NÂ¹-(4-aminophenylsulfonyl)acetamide] bound to carboxyl group of mefenamic acid a well known nonsteroidal anti-inflammatory drugs (NSAIDs) were designed and synthesized for evaluation as a potential anti-inflammatory agent.  In vivo acute anti-inflammatory activity of the final compounds (9, 10 and 11) was evaluated in rat using egg-white induced edema model of inflammation in a dose equivalent to (7.5mg/Kg) of mefenamic acid. All tested compounds produced a significant reduction in paw edema with respect to the effect of propylene glycol 50% v/v (control group). Moreover, the 4-amino-N-methylbenzenesulfonamide derivative (compound 10) exhibited comparable anti-inflammatory activity to diclofenac (3mg/Kg) at times 180-300 minute with the same onset of action. The results of this study indicate that the incorporation of the 4-aminobenzenesulfonamide pharmacophore and its derivatives in to mefenamic acid maintain its anti-inflammatory activity. Key ward: benzenesulfonamide, anti-inflammatory, paw edema, NSAIDs, mefenamic   acid